Patient and parent perspectives on transition from paediatric to adult healthcare in rheumatic diseases: an interview study. Issue 1 (4th January 2021) - Jiang, Ivy; Major, Gabor; Singh-Grewal, Davinder; Teng, Claris; Kelly, Ayano; Niddrie, Fiona; Chaitow, Jeffrey; O'Neill, Sean; Hassett, Geraldine; Damodaran, Arvin; Bernays, Sarah; Manera, Karine; et al.
Abstract : Objectives: To describe the experiences, priorities, and needs of patients with rheumatic disease and their parents during transition from paediatric to adult healthcare. Setting: Face-to-face and telephone semistructured interviews were conducted from December 2018 to September 2019 recruited from five hospital centres in Australia. Participants: Fourteen young people and 16 parents were interviewed. Young people were included if they were English speaking, aged 14–25 years, diagnosed with an inflammatory rheumatic disease (eg, juvenile idiopathic arthritis, juvenile dermatomyositis, systemic lupus erythematosus, panniculitis, familial Mediterranean fever) before 18 years of age. Young people were not included if they were diagnosed in the adult setting. Results: We identified four themes with respective subthemes: avoid repeat of past disruption (maintain disease stability, preserve adjusted personal goals, protect social inclusion); encounter a daunting adult environment (serious and sombre mood, discredited and isolated identity, fear of a rigid system); establish therapeutic alliances with adult rheumatology providers (relinquish a trusting relationship, seek person-focused care, redefine personal–professional boundaries, reassurance of alternative medical supports, transferred trust to adult doctor) and negotiate patient autonomy (confidence in formerly gained independence, alleviate burden on patients, mediate parental anxiety). Conclusions: During transition, patients want to maintain disease stability, develop a relationship with their adult provider centralised on personal goals and access support networks. Strategies to comprehensively communicate information between providers, support self-management, and negotiate individualised goals for independence during transition planning may improve satisfaction, and health and treatment outcomes.